Knowledge and perceptions of doping practices and anti-doping education among elite North American female triathletes - Masucci, M. A.; Butryn, T. M.; Johnson, J. A. (Performance Enhancement & Health, 2019)
The main purpose of this study was to investigate knowledge of doping practices and anti-doping education among American and Canadian female professional triathletes. The second purpose of this study was to examine the potential motivating factors to engage in prohibited doping, as well as to better understand athletes` reasons for and/or impediments to refrain from doping practices. Six Canadian and six American female professional triathletes (n = 12) participated in semi-structured interviews (Sparkes & Smith, 2014) that lasted between 35 min and 90 min. The interview guide (see Appendix A) consisted of questions related to athletes` experiences of anti-doping education, knowledge of doping, and experiences with drug-testing procedures. The inductive thematic analysis of the transcript data yielded four major themes including, 1) changes in the sport over last 15 years; 2) perceptions of prevalence and availability of doping; 3) perceptions of anti-doping efforts and; 4) perceptions and experiences of anti-doping education approaches. The results may help to inform anti-doping education programs at the national and international levels and speak to the need for a more coherent and communicative approach to anti-doping. This study constituted the second phase of a World Anti-Doping Agency (WADA) supported Social Science initiative.